2004
DOI: 10.1075/lald.36.14cla
|View full text |Cite
|
Sign up to set email alerts
|

Lexical and morphological skills in English-speaking children withWilliams syndrome

Abstract: operations to form larger linguistic expressions (e.g. Chomsky 1995, Pinker 1999), we proposed that these two core modules of language are dissociated in WS such that the computational (rule-based) system for language is selectively spared, while lexical representations and/or their access procedures are impaired (Clahsen & Almazan 1998, Clahsen & Temple 2003). This account of the linguistic difficulties of children with WS has recently been challenged by Thomas, Karmiloff-Smith and their collaborators, on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
49
2
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 16 publications
9
49
2
1
Order By: Relevance
“…Thus, there is a dramatic reduction in the production of over-regularized past tense forms with age, although over-regularization continues into adulthood for many individuals with Williams syndrome. The interpretation of the English past-tense findings is a subject of vigorous debate between researchers who consider the data to support a dual-mechanism model of language that is compatible with the existence of an independent grammar module [Clahsen and Almazan, 1998;Clahsen et al, 2003;Marshall and van der Lely, 2006] and those who consider the same data to support a single-mechanism model [Thomas et al, 2001;Thomas and Karmiloff-Smith, 2003]. The resolution of this debate is likely to depend on longitudinal studies of past tense acquisition.…”
Section: Grammarmentioning
confidence: 95%
See 1 more Smart Citation
“…Thus, there is a dramatic reduction in the production of over-regularized past tense forms with age, although over-regularization continues into adulthood for many individuals with Williams syndrome. The interpretation of the English past-tense findings is a subject of vigorous debate between researchers who consider the data to support a dual-mechanism model of language that is compatible with the existence of an independent grammar module [Clahsen and Almazan, 1998;Clahsen et al, 2003;Marshall and van der Lely, 2006] and those who consider the same data to support a single-mechanism model [Thomas et al, 2001;Thomas and Karmiloff-Smith, 2003]. The resolution of this debate is likely to depend on longitudinal studies of past tense acquisition.…”
Section: Grammarmentioning
confidence: 95%
“…A few researchers [e.g. Clahsen and Almazan, 1998;Clahsen et al, 2003;Marshall and van der Lely, 2006] argue for a limited modularity position in their discussions of the acquisition of the past tense by children and adolescents with Williams syndrome. Other researchers set out to investigate the modularity position but conclude that their data are not supportive [e.g.…”
mentioning
confidence: 99%
“…Indeed, WS children made more errors than a group of typically developing children matched on mental age in tests assessing relative clause production (Zukowski, 2004) and grammatical gender agreement . In the specific case of inflectional morphology, it has been suggested that rule-based inflectional morphology may be spared, whereas irregular inflection may be impaired (Clahsen, Ring, & Temple, 2004). However, in some cases, both regular and irregular inflectional morphology were found impaired in WS individuals (Thomas et al, 2001).…”
Section: Introductionmentioning
confidence: 97%
“…Rare words emerge in spontaneous speech because frequency has not been encoded into the lexicon in the normal way (for example, because the base-rate activation of lexical entries has not been set at a level that appropriately reflects their frequency of usage; see e.g., McClelland & Rumelhart, 1981); or because the lexical retrieval process has developed inadequately to the extent that it mistakenly retrieves not-quite-appropriate, lower-frequency words in a given semantic context. Proposals of this sort include the following claims: (1) that word retrieval is deviant in WS ; (2) that while word knowledge may be well organised, inhibitory activation dynamics which integrate current contextual information are abnormal in lexical access (Rossen et al, 1996); (3) that lexical access is fast but sloppy in WS, with inadequately specified semantic representations (Temple, Almazan, & Sherwood, 2002); and more precisely, (4) that children with WS cannot access fine-grained semantic features of lexical items (Clahsen, Ring, & Temple, 2003). Claims of domain-specific atypicalities in the WS lexicon are often associated with a broader perspective of WS as a developmental fractionation of the normal cognitive-and in this case-language system, whereby the WS system is viewed in terms of the architecture of the normal system but with selective components of the system under-or over-developed (Temple & Clahsen, 2002;see Karmiloff-Smith, 1998, andKarmiloffSmith, 2002, for discussion).…”
Section: Introductionmentioning
confidence: 99%